Lenvatinib-induced severe generalized erythematous rash in a patient with hepatocellular carcinoma - Yukari Matsumoto; Takeshi Fukumoto; Wakako Takahashi; Chikako Nishigori (PAGEPress Publications, 2022)
Lenvatinib, an oral multikinase inhibitor, is a first-line drug for the treatment of unresectable hepatocellular carcinoma. Here, we report a case of a 72-year-old man who presented with severe generalized erythematous rash (GER) approximately four weeks after the commencement of lenvatinib treatment, which he had been receiving for the treatment of unresectable lung metastases stemming from hepatocellular carcinoma. The patient had suffered from ichthyosis since his childhood, which made the diagnosis difficult. He had been diagnosed with dermatomycosis of the skin of whole body and treated by terbinafine tablets and luliconazole cream at another hospital. After remission of GER, lenvatinib was readministered because the patient's metastatic lung tumor enlarged, which led to a recurrence of erythema with pruritus on the upper part of patient's body. We confirmed the diagnosis of Lenvatinib-induced generalized GER based on the positive result of the patch test after the informed consent. To the best of our knowledge, this is the first detailed case of lenvatinibinduced GER. Raising physicians' awareness of this potentially severe adverse effect is of importance because of lenvatinib's increasing prominence as the drug of choice in cancer therapy.